Clinical and anamnestic characteristics of patients with clinical manifestations of peripheral artery disease as a function of Т(–786)С polymorphism of the endothelial NO-synthase gene promoter - V.I. Tseluyko; L.M. Yakovleva; O.D. Yarova (Кардіохірургія та інтервенційна кардіологія)
The aim – to determine the prevalence of Т(–786)С polymorphic gene variants of endothelial NO-synthase (eNOs) in patients with verified atherosclerosis of lower extremities arteries and their association with clinical manifestations of the disease. Materials and methods. The study involved 100 patients with verified peripheral artery disease (PAD) of the lower extremities. The control group included 35 people without changes of coronary arteries and with negative result of exercise stress test. The examination, apart from clinical tests, included determination of ankle-brachial index, selective coronary angiography, Doppler ultrasound of the lower extremities and carotid arteries as well as the estimation of their intima – media thickness. The study of allelic polymorphism of eNOs gene promoter was performed by polymerase chain reaction. Results. According to the results of genotyping of Т(–786)С gene polymorphism of eNOs the share of T/T genotypes in the control group (45.7 %) and in patients with PAD (33 %) was not different (р = 0.18), and C/T more frequently found in the control group (48.6 % vs 26 %; p = 0.01), whereas the prevalence of the C/C genotype in patients with PAD was significantly higher than in healthy individuals (41 % vs 5.7 %; p = 0.0001). The patients were divided into three groups: I group – 33 people with T/T genotype, II group – 26 people with C/T genotype and IІI group – 41 people with C/C genotype. The average age of the manifestation of PAD in patients with genotype C/C was significantly lower (50.15 ± 0.63 years) than in the group with the T/T genotype (58.45 ± 1.17 years; p = 0.001) and С/T (53.53 ± 1.28 years; p = 0.01). It was found that in the ІІІ group patients have more severe clinical manifestations of arterial insufficiency of lower limbs (according to Fontaine classification). The patients with C/C genotype had more severe course of the coronary artery disease (CAD): myocardial infarction in ІІІ group was 31.7 % (13) (vs 3.0 % (1) in І group, р = 0.005 and 7.7 % (2) in ІІ group, р = 0.045); the stable angina of ІІІ functional class was detected significantly more often in ІІІ group (29.3 % (12) vs 3 % (1), p = 0.008). Conclusions. The development of the PAD may be partly related of Т(–786)С polymorphism of the eNOs gene promoter, as evidenced by 2.74 times (p = 0.001) greater incidence of minor C allele genotype in these patients than in healthy individuals. The results of the study indicate that patients with C allele polymorphism Т(–786)С eNOs gene promoter have manifestation of the disease in younger age, clinical manifestations of lower limb ischemia is a severe, concomitant CAD is diagnosed significantly more often.